Biofortification: Future Challenges for a Newly Emerging Technology to Improve Nutrition Security Sustainably - Howarth Bouis; Jennifer Foley; Keith Lividini; Jaya Jumrani; Russell Reinke; Dominique Van Der Straeten; Ronan Zagado; Erick Boy; Lynn R Brown; Bho Mudyahoto; Richard Alioma; Munawar Hussain; et al. (Current Developments in Nutrition)
Biofortification was coined as a term to define a plant breeding strategy to increase the micronutrient content of staple food crops to reduce the burden of micronutrient deficiencies in low- and middle-income countries. In 2003, the HarvestPlus program, based in the centers comprising the Consultative Group on International Agricultural Research, was initiated to implement the biofortification strategy. This article discusses what has been achieved, what has been learned, and the key challenges to embed biofortification in food systems and to expand its impact. Cost-effectiveness is key to the biofortification strategy. Biofortification piggybacks on the agronomically superior varieties being developed at agricultural research centers. Central plant breeding research discoveries can be spread globally. Farmers have every motivation to adopt the latest high-yielding, high profit crops. High productivity leads to lower food prices. As a consequence, consumers can increase their mineral and vitamin intakes at no additional cost by substituting biofortified staple foods 1-for-1 for nonbiofortified staple foods. After 20 years of investment, biofortified staple food crops are being produced by farmers in over 40 countries and are eaten by hundreds of millions of people. Published nutrition trials have shown nutrient-rich crops to be efficacious. The biofortification strategy is now recognized by the international nutrition community as one effective approach among several interventions needed to reduce micronutrient deficiencies. This is a promising beginning. However, biofortification is still a newly emerging technology. A limitation of biofortification as implemented to date is that densities of single nutrients have been increased in given staple food crops. To reach a higher trajectory, the impacts of biofortification can be multiplied several-fold using genetic engineering and other advanced crop development techniques to combine multiple-nutrient densities with climate-smart traits.